Stock Market Efficiency in the Time of COVID-19: Evidence from Industry Stock Returns - Lalwani, Vaibhav; Meshram, Vedprakash Vasantrao (International Journal of Accounting & Finance Review, 2020)
Using industry portfolios as test assets and a battery of statistical tests, we study if the informational efficiency of stock prices has declined after the COVID-19 crisis began. The results suggest that the predictability of stock returns in some industries has increased during the COVID-19 period. Markets appear to have become less informationally efficient during the COVID-19 crisis. JEL Classification Code: C58, G01, G10, G14.